Genetics of progressive multifocal leukoencephalopathy: update on case reports with an inborn error of immunity and risk variants found in drug-linked cases - Eis, Peggy S.; Smith, Edward B.; Jalilzadeh, Shapour; Hatchwell, Eli (Frontiers in Neurology, 2025)
A genetic predisposition to PML is now substantially supported by case reports of patients molecularly diagnosed with an inborn error of immunity (IEI) and progressive multifocal leukoencephalopathy (PML). Over the past 10 years, 4 IEI genes linked to PML has now grown to 26 as of 2025. Of these 26 genes believed to be causal of an IEI and PML, 24 (92%) are also linked with hemophagocytic lymphohistiocytosis/macrophage activation syndrome (HLH/MAS)—a severe hyper-inflammation syndrome associated with several IEI genes, most notably in 4 genes (PRF1, STX11, STXBP2, UNC13D) causing familial forms of the syndrome. Many HLH-linked genes are associated with life-threatening Epstein–Barr virus infections, which analogously suggests JC virus infection plus presence of a pathogenic variant in an HLH-linked IEI gene also increases risk of PML. PML also occurs as a serious adverse event for a subset of immunosuppressive therapies (e.g., natalizumab and rituximab) used to treat patients with immune disorders (e.g., multiple sclerosis and hematological malignancies). Recently, 4 PML risk variants were reported for use in a PML risk test to screen patients who are considering treatment with PML-linked therapies. Interestingly, of the 4 genes with a PML risk variant, 2 (LY9 and STXBP2) cause or are linked to HLH. The aim of our review is two-fold: (1) raise awareness among researchers and clinicians (e.g., neurologists, oncologists, and rheumatologists) that patient genetics are a key risk factor for PML, and (2) further reinforce the rationale for screening at-risk patients for PML risk variants before prescribing a PML-linked drug.